Calculating the Ultimate Bearing Capacity of a Strong Soil Layer over a Weak Soil Layer - A. A. Shanaa, Maha (International Journal of Engineering Research, 2023)
The ultimate bearing capacity calculations for shallow footings in two-layered soil systems hinge on the underlying failure surface pattern. his study examines scenarios observed in nature, where strong soil overlays a weaker layer within layered soils, specifically focusing on square footings and calculation of the ultimate bearing capacity value using different theoretical equations according to the approaches of the scientists Terzaghi, Hansen, Meyerhof, and Vesic. an analysis of the values of the results and compared with each other. Presented the results of the study for the ultimate bearing capacity of layered [C - Ꝋ] soils are stronger than all studied soils cases and the ultimate bearing capacity of sandy layered soils is times stronger than the ultimate bearing capacity of clayey layered soils, As that ultimate bearing capacity of clayey layered soils is weaker than all studied soils cases.